Study of the turbocharger shaft motion by means of infrared sensors. (May 2015) - Serrano, J.R.; Guardiola, C.; Dolz, V.; López, M.A.; Bouffaud, F.
Abstract: This work describes a technique for measuring the precession movement of the shaft of small automotive turbochargers. The main novelty is that the technique is based on infrared light diode sensors. With presented technique it is possible to perform secure mounting of electronics and also to measure, with good accuracy, far enough from the turbocharger shaft. Both advantages allow applying it even in critical lubrication conditions and when blade contact occurs. The technique׳s main difficulties arise from the small size of the turbocharger shaft and the high precession movement in critical conditions. In order to generate the optimum albedo reflection for infrared measurement, a special cylindrical nut with larger diameter than the original one is assembled at the shaft tip in the compressor side. Following, shaft balancing, the calibration of the sensors and the compensation of errors from different sources are needed steps before the method is able to identify the main frequencies of shaft motion. Once synchronous and sub-synchronous frequencies have been obtained it is possible to reconstruct the instantaneous position of the shaft to determine its precession movement. Highlights: Design an infrared optical technique to estimate the shaft motion of a turbocharger in experimental tests. Define all the signal frequency analysis to fix the shaft tip position in the compressor side. Describe the errors of this technique and the proceedings to minimize them. Use this infrared optical technique in a turbocharger test and show the main results.